Tax Policy in MENA Countries : Looking Back and Forward - Mansour, Mario (IMF Working Papers; Working Paper ;, 2015)
This paper reviews trends in taxation and revenue in MENA countries over 1990-2012, with a focus on non-resource taxes. On average, non-resource revenues declined slightly, while resource revenues soared. Country experiences vary: rates of main taxes and their revenues tend to be higher in the Magreb than in the Mashreq, except for the value-added tax, where lower rates are associated with equal or higher revenue; most oil producers raise little tax revenues-generally less than 5 percent of GDP-and most have reduced them since the late 1990s. But there are similarities: unlike common experience around the world, income taxes (not indirect taxes) have partially compensated for lost revenue from trade liberalization; revenues from indirect taxes have remained stable; personal income taxes have played an unimportant role as a revenue tool; and fees and stamp duties are significant revenue sources. Looking forward, tax reform challenges will also vary across countries: the Maghreb needs to focus on efficiency-enhancing reforms, especially in capital income and consumption taxes; the Mashreq have some room to increase revenue; and, there are ample opportunities to improve equity and reduce complexity of tax systems in all countries. Finally, the recent decline in oil prices and revenues is a reminder that even resource-rich GCC countries need to lay the basis of a tax system for the future.